2017
DOI: 10.1097/mao.0000000000001343
|View full text |Cite
|
Sign up to set email alerts
|

Cochlear Implantation in Children With Congenital Single-Sided Deafness

Abstract: Cochlear implant (CI) provision provides children with congenital SSD with significant audiological and subjective benefits which can be seen even in children implanted after the age of 3;6. The problem of limited use and nonuser, however, should not be ignored and has to be considered for further studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
129
2
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 96 publications
(142 citation statements)
references
References 39 publications
8
129
2
3
Order By: Relevance
“…The SSQ questionnaire results showed significant improvements in the three sub‐scales studied. This established a high score in the CI satisfaction parameter by the parents regardless of the age of implantation; these results are similar to those obtained in other studies . According to previous studies, both bilateral CI and unilateral CI + HA groups achieved high rates of open‐set speech perception.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…The SSQ questionnaire results showed significant improvements in the three sub‐scales studied. This established a high score in the CI satisfaction parameter by the parents regardless of the age of implantation; these results are similar to those obtained in other studies . According to previous studies, both bilateral CI and unilateral CI + HA groups achieved high rates of open‐set speech perception.…”
Section: Discussionsupporting
confidence: 89%
“…Thomas et al demonstrated in their study performed on children with single‐sided deafness that the post‐operative hearing benefit was significant in the auditory tests for understanding speech in noise . In our study, all the children suffering from congenital SSD were aged ≤5 years, so we have no results related to the speech discrimination improvement; however, with respect to the subjects suffering from acquired SSD, the results in discrimination reached values above 50% in all the modalities studied.…”
Section: Discussionmentioning
confidence: 49%
See 2 more Smart Citations
“…As an emerging treatment in the SSD population, longitudinal studies are lacking. It's relevant to mention that in a study of 21 children with congenital SSD, Thomas et al reported that in those with more than 3 years of follow-up, 3/5 children were limited users or non-users of their CI [82]. This information becomes crucial for practical clinical decisions, cost-effective treatments and patient/parent counseling.…”
Section: Cochlear Implantationmentioning
confidence: 99%